Comparative studying of morphological features of fruits of Crataegus ambigua C.A.Mey. in gorges of West Karatau (Experimental biology, 2016)
Results of morphological features variability studying of Crataegus ambigua C.A.Mey fruits innatural Mangistau populations are presented in article. The variation coefficient, indexes and signs of fruits is applied to morphological featuresvariabilitystudying. It is established that in each of the studied gorges individual variability fluctuates in different limits and depends on ecological conditions of growth. A comprehensive study of the morphological features of hawthorn fruit questionable in natural populations allows to choose plants for the introduction of a culture is not random, but taking into account the most economically valuable forms with a rich reserve of genetic variation.
Keywords: Crataegus ambigua; morphology of fruits; variation coefficient; indexes of fruits; signs of fruits.